Pembelajaran Kitab Kuning di SMP Fauzaniyyah Sukaresmi Garut untuk Mencetak Siswa Unggul - Inayatulloh, Supyan; Sukandar, Ahmad; Setiawan, Marwan (Edukasi: Journal of Educational Research, 2022)
Human nature is a social creature which according to Aristotle is called the "Zoon Politicon". In an effort to socialize, humans group or enter a group or organization, in an organization then when someone stands out, recognizes their strengths and influences and moves joint efforts in achieving a predetermined goal, they are called leaders. This research uses an organization that is a school educational institution. Educational leaders must have a commitment to quality improvement in their main functions. Therefore, the functions of educational leadership must be focused on the quality or quality of learning. The quality of education is a direct consequence of a change and development of various aspects of life. There are various styles of heads in implementing and developing leadership activities, namely authoritarian leadership style, Laissez Faire leadership style, democratic leadership style. On that basis, this research focuses on the limitations of the problem in the study, there are two, namely: 1) How is the Quality of Islamic Religious Education in Fauzaniyyah Middle School?; and 2) How to learn the Yellow Book in junior high schools to produce excellent students in educational institutions. Furthermore, this study uses qualitative research methods using a case study plan on the leadership style of school principals in improving the quality of Islamic religious education. The results of this study indicate that (1) the quality of Islamic Religious Education in SMP Fauzaniyyah can be said to be quite good, this can be seen in terms of input, process and output. In terms of input, the students of SMP Fauzaniyyah have the motivation to always improve themselves in achieving according to their talents and abilities, teachers, staff, TU, counselors and administrators who have expertise in their fields and are also supported by adequate infrastructure. In terms of process, Islamic religion teachers at Fauzaniyyah Junior High School have used various teaching methods so that it is easy for students to understand PAI material. As for the output, most of the graduate students are accepted in top universities, are diligent in praying and can read the Qur'an. (2) Principal Fauzaniyyah's leadership style in improving the quality of Islamic religious education is more likely to use a democratic (participatory) leadership style. In this case the principal prioritizes deliberation and consensus in solving a problem. But often in certain situations or conditions require the principal to act differently (authoritarian).